THE IMPACT OF GAMIFICATION ON ENGLISH VOCABULARY ACQUISITION - Maxmanazarova Feruza Ismoilovna; Qudratova Guliza (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This study explores how gamification transforms English vocabulary acquisition for university students. Findings reveal that integrating game elements significantly boosts motivation and memory retention while reducing learning anxiety. Ultimately, gamified tools turn repetitive memorization into a dynamic and interactive educational experience.